Seamount seascape composition and configuration shape Southwest Indian Ridge fish assemblages - Swanborn, DS; Huvenne, VAI; Malpas, T; Pittman, SJ; Rogers, AD; Taylor, ML; Woodall, LC (Elsevier, 2022)
Seamounts are commercially important fishing grounds. Yet, little is known about their physical characteristics as fish habitat, important for informing conservation and ecosystem-based management.